PROSPECTS FOR THE APPLICATION OF VERTICAL AXIS WIND TURBINES IN THE JIZZAKH REGION - Khudoyberdiev, Umid (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
Foreign and local researchers analyzed the wind energy potential, and technical and economic indicators of Bukhara, Navoi, Karakalpakstan, Kashkadarya, and Tashkent regions. However, the information obtained as a result of the study about the potential of wind energy in the Jizzakh region, its direction, and technical indicators is insufficient. In this article, analyzing the potential of wind energy in the Jizzakh region, the prospects for the use of small vertical wind energy devices are explored.